Optimalisasi Daya Tarik Wisata Kampoeng Kopi Banaran di Kabupaten Semarang - Dewi Krisdayanti Waruwu; Aurilia Triani Aryaningtyas (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2025)
Kampoeng Kopi Banaran is an agrotourism destination in Semarang Regency with significant potential to attract tourists. This study aims to analyze the current tourism appeal of Kampoeng Kopi Banaran, identify influencing factors through a SWOT analysis, and formulate development strategies to increase the number of visitors. The research method used is descriptive qualitative, with data collection techniques including interviews, observations, and document studies. The findings indicate that Kampoeng Kopi Banaran's main attractions are its coffee plantation landscape and coffee processing education. However, several weaknesses were identified, such as a lack of innovative tourism attractions, limited infrastructure, and suboptimal digital promotion. The SWOT analysis reveals that the main strength lies in the unique coffee-based tourism experience, while the primary weakness is the lack of diversified tourism activities. Opportunities include the growing trend of experiential tourism and government support, whereas the main threat is competition from other tourist destinations in Semarang. Recommended strategies include product innovation, digital marketing optimization, and infrastructure and facility improvements. With the right strategies, Kampoeng Kopi Banaran can potentially become a leading agrotourism destination in Semarang Regency.